Cost-Effectiveness Analysis Of Pulmicort-Combivent And Pulmicort Single Use In Inpatients With Chronic Obstructive Pulmonary Disease At Dr. Moewardi Regional Hospital - Yustina Esha Maunia Chantika; Kharisma Jayak Pratama; Vivin Marwiyati Rohmana (CV. AFDIFAL MAJU BERKAH, 2026)
Chronic Obstructive Pulmonary Disease (COPD) causes a high economic burden due to repeated hospitalizations, but the cost-effectiveness of Pulmicort-Combivent versus Pulmicort alone has not been evaluated at Dr. Moewardi Regional General Hospital. This study aims to determine ACER, ICER, and cost-effectiveness of therapy using CEA. This study was a retrospective, descriptive, cross-sectional observational study with a total sampling of 62 hospitalized COPD patients from January 2024 to November 2025. Medical record data instruments were analyzed using ACER, ICER, and the Mann-Whitney test. The results showed that the ACER of Pulmicort-Combivent Rp225,775 (40% effectiveness) was lower than that of Pulmicort alone Rp765,036 (14.03%), ICER Rp-65,554, with no significant difference (p>0.05). Both therapies were equivalent in terms of cost-effectiveness.